Studi Pelayanan Kesehatan Melalui Puskesmas di Kabupaten Semarang - Firdania Rarastiti Arisadewi; Turtiantoro .; Supratiwi . (Journal of Politic and Government Studies, 2013)
The Health Ministry in Semarang is health services levy exemption granted by the Government to the entire population of Semarang Regency that has Residents Sign Cards or a family card without exception. Health services levy exemption given is all there is in health services clinics in addition to hospitalization and health tests. The Health Ministry was held with the free highlights to the Ministry to the wider community in order to achieve optimal health degree movies, without neglecting the quality of service to individuals. The Ministry of health centers free start since 2008 and was held for almost 5 years of service free clinics has been going pretty well. In general there are no obstacles in the implementation of the health service means, obstacles that arise more comes from the State of the environment and the situation in each of the locations of clinics like each road conditions, weather conditions or outbreaks of disease.